A SECONDARY ISOTOPIC REFERENCE MATERIAL OF CHLORINE FROM SELECTED SEAWATER - Xiao Y.K.; Yinming Z.; Qingzhong W.; Haizhen W.; Weiguo L.; Eastoe C.J. (My University, 2002)
A secondary isotopic reference material of chlorine as NaCl collected from a sea water, located at 4°18'N, 161°08'E and collected on October 22, 1994, was prepared using ion exchange technique. The δ37Cl of an NaCl product named ISL 354 was measured to be -0.39+/-0.05%% (2σ) related to NIST SRM 975, an isotopic standard reference material with an absolute 37Cl/35Cl ratio of 0.31977. No contamination or isotopic fractionation was observed due to a complete recovery of chlorine and the avoidance of chemical reagents during preparation of ISL 354 from selected seawater. The isotopic composition of chlorine in ISL 354 does not change on long-term storage. So ISL 354 can be used as a secondary isotopic reference material of chlorine.
Keywords: 37CL/35CL; REFERENCE MATERIAL; SEAWATER